Hypertriglyceridemia-Induced Acute Pancreatitis with Lipemic Samples in a Type 2 Diabetic Patient: A Case Report in a Resource-Limited Setting - Ahmed HM; Osman MH; Hassan SA; Dirie HM; Mohamed MA (International Medical Case Reports Journal)
Hussein Mahdi Ahmed,1 Mohamed Hassan Osman,1,2 Shafie Abdulkadir Hassan,2 Hassan Mohamud Dirie,1 Mowlid Abdikarin Mohamed2 1Department of Internal Medicine, Royal Hospital, Mogadishu, Somalia; 2Faculty of Medicine and Health Sciences, Jamhuriya University of Science and Technology, Mogadishu, SomaliaCorrespondence: Shafie Abdulkadir Hassan, Faculty of Medicine and Health Sciences, Jamhuriya University of Science and Technology, Hodon District, Mogadishu, Somalia, Tel +252615206907, Email Shafici@just.edu.soBackground: Hypertriglyceridemia (HTG) is a known but relatively uncommon cause of acute pancreatitis (AP), accounting for approximately 1– 7% of cases. Hypertriglyceridemia-induced acute pancreatitis (HTG-AP) can lead to significant morbidity if not promptly identified and managed. This case report describes a patient with poorly controlled type 2 diabetes mellitus (T2DM) who presented with HTG-AP, characterized by a lipemic blood sample, in a resource-limited setting.Case Presentation: A 45-year-old male with a history of poorly controlled T2DM and hyperlipidemia presented with a 24-hour history of severe epigastric abdominal pain, fatigue, and vomiting. Clinical examination revealed diffuse abdominal tenderness, tachypnea, tachycardia, and a habitus consistent with central obesity. His BMI was 33.2 kg/m². Initial laboratory findings included seriously elevated triglycerides (1509 mg/dL), lipase (83 U/L), and amylase (161 U/L), along with hyperglycemia (465mg/dL). Abdominal computed tomography (CT) scan showed peripancreatic fatty stranding, consistent with early acute pancreatitis, as well as a fatty liver and a focal hypodense lesion in the right lobe. Treatment included intravenous insulin, dextrose, and potassium infusions to reduce triglyceride levels, analgesics, intravenous fluids for electrolyte imbalances, and thromboprophylaxis with enoxaparin.Conclusion: This case highlights the importance of early recognition of HTG-AP in patients with poorly controlled diabetes and hyperlipidemia. Prompt triglyceride-lowering therapy, primarily with insulin in resource-limited settings, is crucial for improving patient outcomes and preventing complications.Keywords: hypertriglyceridemia, acute pancreatitis, diabetes mellitus, triglyceride-lowering therapy, lipemia, case report